دور مبادئ الحوكمة في الرفع من مستوى جودة التقارير المالية في المؤسسات المدرجة في بورصة الجزائر - يمامي ،ساره; نوبلي، نجلاء (جامعة الوادي University of Eloued, 2025)
This study aims to know the role that governance principles play in enhancing the quality of financial reports in institutions listed on the Algerian stock Exchange -a case study of the saidal Group – and this through familiarity with the conceptual framework of corporate governance and the quality of financial reports and the relationship that connects them, and how to benefit from governance principles in achieving that quality In this study , the researchers relied on the descriptive, analytical and inductive approach by distributing a questionnaire to the study population, then unpacking the answers into the statistical package program SPSS, and then analyzing the data. It was concluded that there is a relationship between corporate governance and the quality of reports, as the proper application of governance principles contributes to achieving and increasing the quality of financial reports
The role of governance principles in raising the level of quality of financial reports in institution listed on the Algerian stock Exchange – a case study of the saidal group -
Keywords: حوكمة; مبادئ الحوكمة; تقارير مالية; جودة التقارير المالية; إفصاح و شفافية; governance; principles of governance; financial reports; quality of financial reports; disclosure and transparency.